99 Impacts of Estrus Expression during a Timed-Ai Protocol on Variables Associated with Fertility and Pregnancy Success in Bos Indicus Beef Cows. (1st March 2018) - Schubach, K M; Cooke, R; Brandao, A P; Marques, R; Cerri, R L A
Abstract: This experiment compared ovarian, uterine and conceptus factors associated with pregnancy establishment in Bos indicus beef cows according to estrus expression during a timed-AI protocol. One hundred lactating multiparous Nelore cows received a 2 mg injection of estradiol benzoate and an intravaginal progesterone (P4 ) releasing device on d -11, a 12.5 mg injection of PGF2α on d -4, P4 device removal in addition to 0.6 mg injection of estradiol cypionate and 300 IU injection of eCG on d -2, and timed-AI on d 0. All cows were inseminated by the same technician with semen from a single bull. An estrus detection patch was attached to the tailhed of each cow on d -2, and estrus expression was defined as removal of > 50% of the rub-off coating from the patch on d 0. Overall, 39 cows expressed estrus (EST ), 55 did not express estrus (NOEST ), and 6 cows lost their patch and were removed from the experiment. Transrectal ultrasonography was performed to verify ovulation and corpus luteum (CL ) volume immediately before AI (d 0), on d 7 and 15. After ultrasonography on d 15, 60 cows (29 EST and 31 NOEST) diagnosed without the presence of a CL on d 0, but with a CL greater than 0.38 cm3 in volume on d 7 and 15, were assigned to conceptus collection via transcervical flushing with PBS followed by endometrial biopsy in the uterine horn ipsilateral to the CL. Blood samples were collected for whole blood RNA extraction (d 20) and pregnancy status was verified by transrectal ultrasonography (d 30) in cows not assigned to conceptus collection. Diameter of dominant follicle on d 0 was greater in EST vs. NOEST (13.8 vs. 12.4 mm; SEM = 0.4). Conceptus length and mRNA expression of prostaglandin E synthase and interferon-tau were greater (P . 0.04) in EST vs. NOEST (2.74 vs. 0.98 cm, SEM = 0.59; 22.24 vs. 3.98 fold effect, SEM = 5.62; 8.17 vs. 2.78 fold effect, SEM = 1.72; respectively). Moreover, EST cows diagnosed as pregnant on d 30 had greater (P < 0.01) blood mRNA expression of myxovirus resistance 2 on d 20 compared with NOEST cohorts (57.5 vs. 27.1 fold effect; SEM = 5.05). Hence, estrus expression near the time of AI enhanced pregnancy establishment factors in B. indicus cows, including conceptus growth and mRNA expression of interferon-tau, as well as blood mRNA expression of a interferon-stimulated gene.